Biology : (Merrill, 1991)
Encompassing more than 20,000 terms, the fourth edition of this best-seller is updated by 20% and draws heavily from the editorial contents of Oil & Gas Journal Latinoamérica, as a source of new technical terminology and of the local usage in different Spanish-speaking countries. Included are many new technical and general words, phrases, and abbreviations used in oil and gas exploration, drilling, logging, completion, reservoir engineering, and production. There is a considerable increase in geologic, geophysical, commercial, computer, and legal terminology. Ancillary fields such as electricity, navigation, construction, and ecology are also expanded.